AI and Digital Spirituality: The Transformation of Islamic Religious Education Learning in the Era of Disruption - Malik, Adam; Nadiva, Dewinta Nisa; Abda’u, Alif Maulana (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The era of technological disruption has brought about significant changes in learning processes, including Islamic Religious Education. The integration of Artificial Intelligence (AI) in education not only provides easy access to learning resources but also creates a new phenomenon known as digital spirituality, a form of religious experience formed through interaction with digital media. This research aims to analyze the role of AI in transforming PAI learning and its impact on the development of students' digital spirituality. The method employed is library research using a PRISMA approach to ensure the selection, analysis, and synthesis of literature are conducted systematically and transparently. The results show that AI contributes positively through personalization of religious learning, virtual spiritual mentoring, expanded access to Islamic knowledge sources, and strengthening digital religious practices. However, on the other hand, AI also potentially weakens spiritual dimensions through risks of fragmentation of religious narratives, reduction of contemplative depth, decreased teacher-student interaction, and the emergence of a hybrid Islamic phenomenon that is not entirely coherent with Islamic traditional values. This research confirms that optimizing AI in PAI learning must be accompanied by ethical policies, religious digital literacy, and teacher mentoring to ensure that the formation of digital spirituality remains within the corridor of authentic Islamic values. Thus, AI integration can become a strategic opportunity to build a generation of digitally intelligent, critically-minded, and spiritually strong Muslims in the era of disruption.